Pemberdayaan Perempuan melalui Inovasi Eco Lilin Berbasis Minyak Jelantah: Studi Program KKN MBKM di Kelurahan Simpang Baru - Ahmad Jamaan; Ahmad Lakendra Akbar Nasution; Nawla Farsha Alendro; Salsabilah Salsabilah; Bari Laksamana Nugraha; Devita Meisari Rezeki Siregar; Diska Claudya; Indah Salsa Aulia; Iren Reby Revalisa Tarigan; Jumiyati Jumiyati; Miftahul Gani; Sheila Almahabatilah; Wan Muhammad Zendi Irfani (Unri Conference Series: Community Engagement, 2025)
Household waste, particularly used cooking oil, remains a significant issue in Indonesia. Data from the National Waste Management Information System (2024) show that households contribute 50.8% of the national waste generation. In Simpang Baru, used cooking oil is generally discarded without processing, posing risks to the environment and public health. This study aims to enhance community awareness and skills, especially among women, in transforming used cooking oil into value-added products through the Eco Candle innovation. The research employed a qualitative approach through interviews with 72 respondents and field observations, followed by a workshop on Eco Candle production with housewives from RW 06, 07, and 08. Activities included socialization, hands-on practice in making aromatherapy candles, and continued mentoring. Findings reveal that 28 respondents (38.9%) were unaware of waste benefits, while 44 (61.1%) recognized its potential, but only 18 (25%) had experience managing it. Waste management practices were grouped into four categories: active (19.4%), economic (22.2%), passive (26.4%), and non-management (31.9%). The workshop received positive responses, reflected in participants’ independent practices. These findings highlight the gap between knowledge and practice while underscoring women’s role as agents of change. The Eco Candle program supports SDG 12 by reducing waste, raising awareness, and creating household-based economic opportunities.